SHEBA: Airborne Imaging Microwave Radiometer (AIMR) [NCAR/EOL/RSF] - dorade format (Arctic Data Center, 2015)
This data set includes Airborne Imaging Microwave Radiometer (AIMR) measurements obtained from the NSF/NCAR C-130 aircraft (Tail Number: N130AR) during the Surface Heat Budget of the Arctic Ocean Project (SHEBA). The tar files contain dorade format data.